2020
DOI: 10.3390/ijerph17155416
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Energy Intakes and Physical Activity Levels According to the Presence of Metabolic Syndrome in Korean Elderly People: Korean National Health and Nutrition Examination Survey 2016–2018

Abstract: This study aimed to analyze the differences in energy intake and physical activity (PA) levels according to sex and the presence of metabolic syndrome (MetS) among elderly people in Korea. Data of 3720 elderly people (aged >65 years) were obtained from the Korean National Health and Nutrition Examination Survey (2016–2018). We analyzed PA levels (occupational and recreational PA) and energy intakes (carbohydrate, protein, and fat). The MetS group showed lower levels of moderate intensity recreational PA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 53 publications
0
9
2
Order By: Relevance
“…According to a previous study, participants engaged in high-intensity PA (≥ 60 min per week) had a 63% lower incidence of MetS than those not engaged in high-intensity PA ( Laaksonen et al, 2002 ). In addition, a study of Koreans also reported a significantly lower incidence of MetS in groups participating in regular PA ( Jung et al, 2020 ). Recently, Lacroix et al (2019) reported that middle-aged and elderly women can significantly reduce the risk of cardiovascular disease by performing low-intensity PA, such as gardening, walking in the park, and folding laundry.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, participants engaged in high-intensity PA (≥ 60 min per week) had a 63% lower incidence of MetS than those not engaged in high-intensity PA ( Laaksonen et al, 2002 ). In addition, a study of Koreans also reported a significantly lower incidence of MetS in groups participating in regular PA ( Jung et al, 2020 ). Recently, Lacroix et al (2019) reported that middle-aged and elderly women can significantly reduce the risk of cardiovascular disease by performing low-intensity PA, such as gardening, walking in the park, and folding laundry.…”
Section: Discussionmentioning
confidence: 99%
“…family and friends) is positively correlated with PA level, whereas living alone may promote a decrease in total PA, which may be as a risk factor for increased occurrence of MetS. Comparing our study with ESH and with mixed households (single and mixed-household type) [40], PA at the total PA and recreational moderate levels of elderly people with MetS in the mixed-household type was higher than in our study; therefore, it can be observed that PA among ESH is low. Moreover, when the total PA level of mixed-households and ESH in our study was compared by sex, there was no signi cant difference in the presence or absence of MetS in males by mixed-household type, but there was a signi cant difference in females.…”
Section: Discussionmentioning
confidence: 56%
“…A previous study of 477 people (aged 55-80 years) in Spain found that the MetS group had lower energy expenditure and less leisure-time PA (< 4 MET) than the non-MetS group [39]. Jung et al [40] [42] reported that having someone (e.g. family and friends) is positively correlated with PA level, whereas living alone may promote a decrease in total PA, which may be as a risk factor for increased occurrence of MetS.…”
Section: Discussionmentioning
confidence: 97%
“…Reports have indicated excessive intake of carbohydrates at the expense of other macronutrients in elderly Koreans [40], and a positive association between high carbohydrate intake and risk of MetS in women [41][42][43][44][45]. A typical Korean diet is rich in refined grains, especially white rice and noodles.…”
Section: Discussionmentioning
confidence: 99%